Nurse Compliance in Implementing Post Op Wound Care Standard Operating Procedures - Suprapto Suprapto (Media Keperawatan Indonesia, 2021)
One of the causes of the occurrence of nosocomial infections is the implementation of standard operating procedures, whether implemented properly or not by nurses. Analyzing nurses' compliance in implementing standard operating procedures for post-op wound care. Analytical quantitative research with a cross-sectional research design. The population of surgical inpatient nurses was 32 nurses, with a sample size of 30 nurses with purposive sampling, analysis information used as chi-square. The results of statistical tests show that there is a relationship between education, knowledge, length of work, training, motivation, and nurse compliance in implementing standard operating procedures for postoperative wound care. That there is a relationship between education, knowledge, years of service, training, and motivation with nurses' compliance with the implementation of standard operating procedures for post-op wound care. Improving the quality of care through efforts to develop the capacity of nurses through education and training in wound care for all nurses.